2018
DOI: 10.1029/2018gc007710
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Insights Into the Effect of Sediment‐Hosted Methane Hydrate Morphology on Elastic Wave Velocity From Time‐Lapse 4‐D Synchrotron X‐Ray Computed Tomography

Abstract: A better understanding of the effect of methane hydrate morphology and saturation on elastic wave velocity of hydrate‐bearing sediments is needed for improved seafloor hydrate resource and geohazard assessment. We conducted X‐ray synchrotron time‐lapse 4‐D imaging of methane hydrate evolution in Leighton Buzzard sand and compared the results to analogous hydrate formation and dissociation experiments in Berea sandstone, on which we measured ultrasonic P and S wave velocities and electrical resistivity. The ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 93 publications
3
43
0
Order By: Relevance
“…These authors also note that the majority of pockmarks observed in the upper and lower slope are associated with BSR weakening and terminations. These observations, tied to a significant decrease in seep density in sediments that lie within the gas hydrate stability zone (Kluesner et al, ), are consistent with gas accumulations beneath a zone where interconnected networks of gas hydrate cut off pore space connectivity limiting upward methane advection (e.g., Evrenos et al, ; Riedel et al, ; Sahoo et al, ).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…These authors also note that the majority of pockmarks observed in the upper and lower slope are associated with BSR weakening and terminations. These observations, tied to a significant decrease in seep density in sediments that lie within the gas hydrate stability zone (Kluesner et al, ), are consistent with gas accumulations beneath a zone where interconnected networks of gas hydrate cut off pore space connectivity limiting upward methane advection (e.g., Evrenos et al, ; Riedel et al, ; Sahoo et al, ).…”
Section: Introductionmentioning
confidence: 72%
“…Whether hydrate can occur as discrete cement or interconnected between pores is still not fully resolved, but recent experiments measuring both hydrate saturation ( S h ) and P ‐wave velocity ( V p ) under pressure are consistent with a load‐bearing hydrate model as presented by Konno et al (). Imaging of methane hydrates using synchrotron X‐ray computed microtomography have also shown methane hydrate to form interconnected networks in porous media (Kerkar et al, ; Sahoo et al, ). In the scenario we postulate, the gas‐hydrate permeability seal was breached as Site U1379 uplifted beyond the upper limit of gas hydrate stability, freeing the methane‐rich fluids to migrate upward and initiate carbonate precipitation at the SMT.…”
Section: Resultsmentioning
confidence: 99%
“…This type of hydrate occurrence plays an important role in the specimen skeleton. It is quite difficult for the clusters to roll or be rearranged among the sand particles in the sediment; thus, the specimen will macroscopically show a greater stiffness and strength (Hyodo et al, ; Sahoo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanical models developed for MHBS assume that the increase of strength, stiffness, and dilatancy observed in these sediments is mainly governed by bonding or cementation between the hydrate crystal and the sediment grains (Table ). However, recent pore‐scale observations and geomechanical investigations evidence the lack of true cohesion in MHBS and suggest that the mechanical response of these sediments may not necessarily be governed by sediment bonding/cementation, but rather to kinematic constrictions at pore/grain scale during shearing. In this paper, we develop a new mechanical constitutive model that does not consider hydrate‐bonding effects in its formulation but assumes that the reduction of sediment available void volume and the increase of sediment elastic stiffness during pore invasion with hydrate can explain the greater mechanical properties observed in MHBS.…”
Section: Introductionmentioning
confidence: 99%